Analisis penerimaan dari pelayanan pasien peserta PT. ASKES Indonesia di Rumah Sakit Umum Pusat dr. Sardjito Yogyakarta tahun 1995 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Background: The revenue of hospital from Askes health insurance participants is considered to be very important due to its dominant proportion. Therefore, it is necessary to analyze whether the use of package rate is beneficial for the hospital. The calculation of benefit or loss is conducted in accordance to several parameter, which include:(1) tariff differences